2011
DOI: 10.1271/bbb.100732
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between in Vitro Mucus Adhesion and the in Vivo Colonization Ability of Lactic Acid Bacteria: Screening of New Candidate Carp Probiotics

Abstract: We measured the adhesion of candidate probiotic lactic acid bacteria (LAB) to carp intestinal mucus. The percentage of adherent bacteria varied among strains. Four strains, two with high adhesion and two with low adhesion in vitro, were tested for in vivo colonization ability. Carp were fed LAB-containing feed for 12 d, and then unsupplemented feed until day 33, and the numbers and compositions of intestinal LAB were analyzed during the entire period. LAB with lower in vitro adhesion disappeared quickly from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…The ability of the strains to adhere to human cells was investigated in the Caco-2 intestinal cells following the procedure described by Sugimura et al (2011) modified by Ren et al (2012). Monolayers Caco-2 cells were grown in Dulbecco's Modified Eagle's Medium DMEM (Lonza BE12-604F) supplemented with 10% heatinactivated foetal bovine serum (Gibco 10270-106), penicillin (100 U ml -1 ; Lonza) and streptomycin (100 mg ml -1 ; Lonza), in 24-well (Cellstar 662-160) tissue culture plates, at a concentration of 1.0 x 10 5 cells ml -1 .…”
Section: In Vitro Adherence Assay To Caco-2 Cellsmentioning
confidence: 99%
“…The ability of the strains to adhere to human cells was investigated in the Caco-2 intestinal cells following the procedure described by Sugimura et al (2011) modified by Ren et al (2012). Monolayers Caco-2 cells were grown in Dulbecco's Modified Eagle's Medium DMEM (Lonza BE12-604F) supplemented with 10% heatinactivated foetal bovine serum (Gibco 10270-106), penicillin (100 U ml -1 ; Lonza) and streptomycin (100 mg ml -1 ; Lonza), in 24-well (Cellstar 662-160) tissue culture plates, at a concentration of 1.0 x 10 5 cells ml -1 .…”
Section: In Vitro Adherence Assay To Caco-2 Cellsmentioning
confidence: 99%
“…harveyi (Korkea-Aho et al, 2012;Lazado et al, 2011;Mahdhi et al, 2012;Sugimura et al, 2011;Sorroza et al, 2012;Chabrillon et al, 2005) and help to resist pathogens (Luis-Villasenor et al, 2011). However, it was also reported that probiotics do not dwell in the digestive tract (Ridha and Azad, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, most studies to select strains that can adhere to the epithelium surface have focused on alternative in vitro models, such as propagated human intestinal cell lines (e.g., HT-29 and Caco-2 cells) because of difficulties experienced in studying bacterial adhesion in vivo, especially in humans (Duary et al, 2011). Recently, specific target hosts, including Artemia nauplii (brine shrimp) and Cyprinus carpio (common carp), have been used to validate or screen probiotic potential (Sugimura et al, 2011;Lamari et al, 2014). Unfortunately, these organisms have critical limitations with regard to reflecting the human gut.…”
Section: Short Communicationmentioning
confidence: 99%